2021
DOI: 10.1007/s40544-020-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity of molybdenum disulfide subjected to large compressive strains

Abstract: The friction between a molybdenum disulphide (MoS2) nanoflake and a MoS2 substrate was analyzed using a modified Tomlinson model based on atomistic force fields. The calculations performed in the study suggest that large deformations in the substrate can induce a dramatic decrease in the friction between the nanoflake and the substrate to produce the so-called superlubricity. The coefficient of friction decreases by 1–4 orders of magnitude when a high strain exceeding 0.1 is applied. This friction reduction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…Nowadays, superlubricity, including solid superlubricity [5] and liquid superlubricity [6], has attracted continuously attention in many fields including machinery, energy, aerospace, and biology [7][8][9][10]. As for solid superlubricity, the achievement of extremely low COF (< 0.01) usually relied on a specific structure (e.g., graphite, MoS 2 , a-C:H, and diamond like carbon (DLC) film) [11][12][13][14][15] or a certain atmosphere (e.g., inert gas and vacuum) [16][17][18]. However, for liquid superlubricity, it is much easier to obtain common friction pairs in the atmosphere; therefore, it has wider application.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, superlubricity, including solid superlubricity [5] and liquid superlubricity [6], has attracted continuously attention in many fields including machinery, energy, aerospace, and biology [7][8][9][10]. As for solid superlubricity, the achievement of extremely low COF (< 0.01) usually relied on a specific structure (e.g., graphite, MoS 2 , a-C:H, and diamond like carbon (DLC) film) [11][12][13][14][15] or a certain atmosphere (e.g., inert gas and vacuum) [16][17][18]. However, for liquid superlubricity, it is much easier to obtain common friction pairs in the atmosphere; therefore, it has wider application.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that due to the existence of two-dimensional graphene sheets, the contact area Fig. 82 Effects of grain boundary or in-plain strain on wear or superlubricity of 2D materials [967,968,971,973]. Reproduced with permission from Ref.…”
Section: Simulation In Micro-friction and Superlubricitymentioning
confidence: 99%
“…[971], © The author(s), 2021; Reproduced with permission from Ref. [973], © The author(s), 2022. of DLC-CNS is smaller than that of DLC-CND, which inhibited the movement of CNS, thereby reducing the frictional dissipation of the system and effectively improving the lubricity of CND. The excellent lubricity obtained by using 2D graphene sheets as the additive phase of composites has also aroused the interest of researchers.…”
Section: Simulation In Micro-friction and Superlubricitymentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the movement pattern (i.e., the self-rotation and sliding) of the abrasive particle, as well as the unavoidable defects, can pose dramatic impacts on the tribological performance of the protection film [23][24][25][26][27]. Until now, Nanoscratching (i.e., two-body contact) is mostly adopted to characterize the frictional behaviors of the film [28][29][30], while few studies take attention to the atomistic modeling and simulation of three-body contact of the MoS2 film.…”
Section: Introductionmentioning
confidence: 99%